Strategi Kelembagaan DPRD Provinsi Lampung Dalam Menindaklanjuti Aspirasi Masyarakat Terkait Pembangunan Infrastruktur Jalan (Daerah Pemilihan 1 Kota Bandar Lampung) - Raizanah, Annisa Raisya; Hermawan, Dedy; Atika, Dewie Brima (Jurusan Ilmu Administrasi Publik FISIP Universitas Lampung, 2025)
The Regional House of Representatives (DPRD) plays a strategic role as the regional legislative body in absorbing and following up on public aspirations, particularly in the area of road infrastructure development. This study aims to analyze the institutional strategies of the Lampung Provincial DPRD in addressing community aspirations regarding road infrastructure in Electoral District 1 of Bandar Lampung City, as well as to identify the main challenges faced. This research employed a qualitative method with data collected through interviews, observations, and documentation, and analyzed using the Miles and Huberman interactive model. The findings reveal that the DPRD’s institutional strategy is centered on three aspects: organizational structure, authority, and standard operating procedures (SOPs). Although the organizational structure is formally established, internal coordination has not been fully synergized, authority has not been strategically utilized to advocate for public demands, and the SOPs for managing aspirations through the E-Pokir system lack transparent evaluation mechanisms. Challenges encountered include weak inter-unit synergy, limited human and technological resources, and low public participation. The study recommends strengthening internal coordination, leveraging authority more strategically, improving participatory SOPs, and enhancing community involvement to ensure that the DPRD fulfills its role in a more transparent, accountable, and responsive manner.